Adaptation of the Possibilities for Activity Scale for women encountering cancer (PActS‐W). (4th September 2018) - Pergolotti, Mackenzi; Doll, Kemi M.; Fawaz, Emily O.; Reeve, Bryce B.
Abstract : Background/aim: The original Possibilities for Activity Scale (PActS) examined the internalised societal pressures of older adults with cancer. Previous research found that scores from the original PActS scale were associated with participation in meaningful activity. Women of working age may have different societal pressures than older adults, which could impact their quality of life. Our aims were to (i) adapt the scale specifically for women, (ii) test convergent and structural validity and (iii) test internal consistency reliability. Method: First, we completed a literature review to add new items, then measured psychometric properties of PActS‐W. Findings: A total of 186 women, one month after cancer surgery completed PActS‐W. PActS‐W demonstrated convergent‐related (physical health r  = 0.40, mental health r  = 0.30, P  < 0.01), structural validity (CFI, 0.96; RMSEA, 0.10; IFI, 0.96, NFI, 0.94) and high internal consistency reliability (stratified coefficient α = 0.90). Conclusion: The PActS‐W may be useful for measuring women's internalised societal pressures after encountering cancer, which relates to their quality of life, but further testing is needed.